Histochemical similarities between newborn and leukaemic myeloid cells and their possible significance. Issue 4 (July 1969) - Wolf, Paul L.; Silberberg, Boris; Albert, Samuel; Horwitz, Jerome; Von Der Muehill, Elisabeth
Abstract : The neutrophilic alkaline phosphatase activity of 40 newborns was determined and found to be frequently raised, similarly to a leukaemoid reaction. The newborn neutrophil has strong alkaline phosphatase activity and is unlike the myeloid leukaemia cell which has no alkaline phosphatase activity.